2003
DOI: 10.1128/iai.71.1.580-583.2003
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter pylori Antioxidant Activities with Host Colonization Proficiency

Abstract: To assess the importance of two separate antioxidant activities in Helicobacter pylori, we tested the abilities of strains with mutations in either tpx (encoding thiolperoxidase) or ahpC (encoding alkyl hydroperoxide reductase [AhpC]) to colonize the stomachs of mice. The tpx strain was clearly more sensitive than the parent strain to both oxygen and cumene hydroperoxide. The strain colonized only 5% of the inoculated mice. Two different classes of oxygen-sensitive ahpC mutants in the type strain (ATCC 43504) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
75
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 19 publications
2
75
0
Order By: Relevance
“…Among these, the most abundant one is AhpC. Several functional studies of H. pylori AhpC have shown that the AhpCdeleted mutants have increased sensitivity to oxygen (15), overexpress neutrophil-activating protein (18), and accelerate inactivation of catalase (25). As a member of 2-Cys peroxiredoxins (17,21,31), AhpC has been shown to be Trx-dependent (17,27,32,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, the most abundant one is AhpC. Several functional studies of H. pylori AhpC have shown that the AhpCdeleted mutants have increased sensitivity to oxygen (15), overexpress neutrophil-activating protein (18), and accelerate inactivation of catalase (25). As a member of 2-Cys peroxiredoxins (17,21,31), AhpC has been shown to be Trx-dependent (17,27,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the electron donor flavoprotein (AhpF) used by most bacteria to reduce AhpC was shown to be inactive for the AhpC of H. pylori (21)(22)(23)(24). In addition, some AhpC-deficient mutant strains have been found to have an increase in the expression of neutrophilactivating protein (NapA) (15,18) or a decrease in the activity of catalase (25). Our previous study has also revealed that the transcription and expression of AhpC in H. pylori isolated from duodenal ulcer patients decrease under long-term oxidative stress (Ͼ8 h in 20% O 2 ) (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NapA, a ferritin-like iron-binding protein, is involved in oxidative stress resistance probably through sequestering free iron in the cells (13,14); also, a NADPH quinone reductase (MdaB) confers oxidative stress resistance by maintaining the quinone pool of the cell in the reduced state (15). The disruption of each individual gene for superoxide dismutase, KatA, AhpC, or MdaB affects severely the ability of the bacterium to colonize the host stomach (15)(16)(17)(18), demonstrating the importance of these enzymes in oxidative stress resistance and host colonization.…”
mentioning
confidence: 99%
“…Based on the number of cysteine residue, they are broadly divided into three subfamilies: the typical 2-Cys Prxs, the atypical 2-Cys Prxs and the 1-Cys Prxs [1]. The common function of this ubiquitous and diverse group of enzymes is their ability to reduce a variety of peroxides to their respective alcohols [2,3]. The majority of the determined peroxiredoxine structures belongs to 2-Cys Prxs family, which has received much attention recently [4].…”
mentioning
confidence: 99%